Bio-Electrical Impedance Analysis: A Valid Assessment Tool for Diagnosis of Low Appendicular Lean Mass in Older Adults? - van den Helder, Jantine; Verreijen, Amely M.; van Dronkelaar, Carliene; Memelink, Robert G.; Engberink, Mariëlle F.; Engelbert, Raoul H. H.; Weijs, Peter J. M.; Tieland, Michael (Frontiers in Nutrition, 2022)
Background: Diagnosis of sarcopenia is essential for early treatment of sarcopenia in older adults, for which assessment of appendicular lean mass (ALM) is needed. Multi-frequency bio-electrical impedance analysis (MF-BIA) may be a valid assessment tool to assess ALM in older adults, but evidence is limited. Therefore, we validated the BIA to diagnose low ALM in older adults. Methods: ALM was assessed by and a standing-posture 8-electrode MF-BIA (Tanita MC-780) in 202 community dwelling older adults (age ≥ 55 years), and compared with dual-energy X-ray absorptiometry (Hologic Inc., Marlborough, Massachusetts, USA; DXA). Validity for assessing absolute values of ALM was evaluated by: 1) bias (mean difference), 2) percentage of accurate predictions (within 5% of DXA values), 3) the mean absolute error (MAE) and 4) limits of agreement (Bland-Altman analysis). The lowest quintile of ALM by DXA was used as proxy for low ALM (<22.8kg for males, <16.1kg for females). Sensitivity and specificity of diagnosing low ALM by BIA were assessed. Results: Mean age of the subjects was 72.1±6.4y, with a BMI of 25.4±3.6kg/m2, and 71% were females. BIA slightly underestimated ALM compared to DXA with a mean bias of 0.6±1.2kg. The percentage accurate predictions was 54% with a MAE of 1.1kg, and limits of agreement were 3.0 to +1.8kg. Sensitivity for ALM was 80%, indicating that 80% of subjects that were diagnosed as low ALM according to DXA were also diagnosed low ALM by BIA. Specificity was 90%, indicating that 90% of subjects who were diagnosed as normal ALM by DXA were also diagnosed as normal ALM by the BIA. Conclusions: This comparison showed a poor validity of MF-BIA to assess absolute values of ALM, but a reasonable sensitivity and specificity to recognize the community-dwelling older adults with the lowest muscle mass.